The literary reception of Old Norse myth in medieval Iceland - Hart, M (2017)
This thesis addresses the incorporation of mythological patterns, characters, and motifs in selected Íslendingasögur (sagas of Icelanders) and fornaldarsögur (sagas of ancient times). Taking as its point of departure the conclusions of Margaret Clunies Ross in Prolonged Echoes, according to which Old Norse myth retained its cultural and conceptual relevance in medieval Iceland and Scandinavia even after conversion, this thesis explores the ideological implications of mythological patterns, characters, and motifs as they are used in saga literature. The thesis begins by demonstrating the way in which mythology was used by saga writers to conceive of and configure rulership and power, including coverage of Snorri's historicization of Old Norse myth to produce a typological model of right rulership in Ynglinga saga, while the assimilation of Óðinn to the figure of the foster-father is attributed to a focus on the god's associations with battle and heroes. Blanket categorizations of the poets of the skáldasögur (sagas of poets) as Odinic figures are revealed to be unwarranted, and non-Odinic material used in the representation of these poets, such as the employment of motifs borrowed from the swan-maiden tale-type in Gunnlaugs saga, is shown to be just as important as Odinic material in conceiving of poets in these sagas. In Chapter 4, a less oppositional binary between gods or humans and giants than has hitherto been acknowledged is suggested, and arguments are made in favour of considering giants to be representative of alternative, peripheral, and decentralizing ideologies. The final chapter argues that practitioners of magic are representative of potential social and political disruption and that that disruption is frequently configured in terms of the mythological outsider, such as the dwarf. This thesis concludes that Old Norse myth was of vital cognitive importance in constructing and negotiating social, cultural, and political ideologies from the twelfth century onwards.